Comparable Postoperative Pain Levels Using 2 Different Nerve Blocks in the Operative Treatment of Displaced Intra-articular Calcaneal Fractures. (December 2017) - Dingemans, Siem A.; de Ruiter, Kristian J.; Birnie, Merel F. N.; Goslings, J. Carel; van Samkar, Gan; Schepers, Tim
Background: The aim of this study was to compare the postoperative pain levels in patients undergoing osteosynthesis of the calcaneus with either a popliteal nerve block or an ankle block. Methods: A retrospective analysis of all consecutive patients undergoing operative fixation of a calcaneal fracture via a sinus tarsi approach between August 2012 and April 2017 in a single foot/ankle specialized center was performed. Single-shot popliteal blocks were placed using ultrasound guidance by an anesthesiologist while ankle blocks were placed by a foot/ankle specialized surgeon. Pain levels were measured through the numerical rating scale (NRS). In total, 83 patients were included in this study; 33 received a popliteal block, and 50 received an ankle block. No statistically significant differences were present in baseline characteristics between the 2 groups. Results: Comparable postoperative pain levels were observed in both groups. There was no statistically significant difference in amount of morphine used between the 2 groups. Conclusion: No differences were found in postoperative pain levels between patients receiving a single-shot popliteal block and patients who received a single-shot ankle block following calcaneal fracture surgery. Level of Evidence: III, comparative series.